Development of cytocompatible protein-based hydrogels crosslinked using tetrakis(hydroxymethyl)phosphonium chloride. Issue 8 (23rd March 2023) - Pandit, Jatin Jawhir; Shrivastava, Archita; Bharadwaj, Tanmay; Verma, Devendra
Abstract : Gelatin, a collagen derivative, possesses excellent properties such as high biocompatibility, high bioactivity, biodegradability, and low immunogenicity, making it an ideal candidate for developing hydrogels for biomedical applications. Abstract : Gelatin, a collagen derivative, possesses excellent properties such as high biocompatibility, high bioactivity, biodegradability, and low immunogenicity, making it an ideal candidate for developing hydrogels for biomedical applications. Gelatin hydrogels are often used in conjunction with other compounds and crosslinkers to improve their physicochemical properties. Tetrakis(hydroxymethyl)phosphonium chloride (THPC) is an amine-reactive crosslinker used previously for hydrogel preparation. However, its usage is limited due to its cytotoxicity at higher concentrations, mainly due to the formation of formaldehyde as a reaction intermediate. Herein, we report gelatin hydrogels crosslinked with THPC along with a novel thermal treatment method to improve the cytocompatibility of the developed hydrogels. Furthermore, LAPONITE® has been incorporated into the proposed hydrogels to further enhance its cytocompatibility along with physicochemical properties. The method of thermal treatment significantly improved the cell viability from ∼20% to ∼60% at a high THPC concentration of 8 mM which was further increased to ∼80% with LAPONITE® incorporation. Thermal treatment also increased the degradation time of hydrogels from ∼9 days to ∼18 days and LAPONITE® incorporation further increased it to ∼22 days at 8 mM THPC concentration. Based on the results, it can be concluded that the thermal treatment method can be an ideal choice for improving the cytocompatibility of THPC-based hydrogels and the synergistic effects of LAPONITE® and thermal treatment can make these hydrogels an ideal candidate for biomedical applications.